Кирк-Єрський скарб ХV ст. (попереднє повідомлення) - Майко, В.В. (Археологія, 2003)
20 березня 2002 р. під мас проведення археологічних досліджень біля входу, що веде до гідротехнічної споруди співробітники центру спелеотуризму «Онікс-Тур» м. Сімферополя на глибині 45 см від рівня сучасної денної поверхні знайшли скарб . Він налічував 4259 срібних, 1 мідну та ЗО золотих монет, а також срібну накладку. Скарб знаходився у кухонному горщику третьої чверті XV ст. Золоті монети були розміщені серед срібних та акуратно загорнуті купкою у шматок тканини. В статье проанализирован клад, обнаруженный в 2002 г. к западу от южных ворот городища Чуфут-Кале, состоящий из 4259 серебряных, 1 медной и 30 золотых монет. Все золотые монеты, кроме одной, — это венецианские дукаты, чеканенные при 8 дожах XIV—XV вв. Одна монета — предположительно чеканки Барс-Бея (1420—1438).
Примерно половину всех серебряных монет (2102 щт.) составляют аспры так называемой татаро-генуэзской чеканки, среди которых преобладают экземпляры с двузубой тамгой. Остальная часть клада — монеты без генуэзских черт. Первая категория — дирхемы Узбека 720, редко 713 Р.Х., в том числе с контрамарками, вторая — монеты Хаджи-Гирея, третья — дирхемы с двузубой тамгой, четвертая — дирхемы золотоордынских ханов: Токты, Узбека, Тохтамыша, Тимур-Кутлука, Шадибека, Пулад-хана, Джелалед-Дина, Керим-Бирди, Кибак-хана, Чегре-хана, Дервиша, Улу-Мухаммеда, 31 монету определить сложно. В кладе есть молдавский грош Александра Доброго и византийская монета Иоанна V Падеолога. Единственная медная монета — первой
четверти XV в. Время тезаврации клада — начало 70-х гг. XV в. Большинство монет приходится на 20-е — 30-е годы XV в. The article deals with buried treasure, which was discovered westwards of the south gate of Chufut-Cale hillford in 2002, containing 4259 silver, 1 copper and 30 golden coins. All the golden coins, except one, are Venice ducats, minted under 8 doges of the 14th—15th century. One coin was minted supposedly by Bars-Bey (1420—1438).
Approximately half of all silver coins (2102 specimens) are aspres of the so-called Genoa- Tatars coinage, among which specimens with two-tines tamga dominate. The second part of treasure trove is coins without Genoa features. The first category contains dirhems of Uzbek 720 y. h., seldom of 713 y. h., including the coins with countermarks (1829 specimens), the second category contains dirhems of Hadzhi-Girey (42 specimens), the third one is dirhems with two-tines tamga (214 specimens), the fourth category contains dirhems, which are minted by the khans of Golden Horde (68 specimens), such as Tokta (1), Uzbek (1), Tohtamysh (l), Timur-Kutluk (1), Shadibek (4), Pulad-khan (2), Dzhelal-ed-Dyne (I), Kerim-Birdi (1), Kibak-khan (1), Chegre-khan (5), Dervish (2),. 31 coins are defined with difficulty. The buried treasure has one Moldavian grosh of Alexander the Kind and one Byzantine coin of John V Palaeologus. Only copper coin dates from the first half of the 15th century. The time of thesauretion of this treasure trove is the beginning of 70th years of 15th-century. Over whelming majority of the coins dates from 20th—30lh years of the I5th century.